The Association Between Patient-Centered Communication and Primary Care Quality in Urban China: Evidence From a Standardized Patient Study - Su, Min; Zhou, Zhongliang; Si, Yafei; Fan, Xiaojing (Frontiers in Public Health, 2022)
Background Effective patient-physician communication has been considered a central clinical function and core value of health system. Currently, there are no studies directly evaluating the association between patient-centered communication (PCC) and primary care quality in urban China. This study aims to investigate the association between PCC and primary care quality. Methods The standardized patients were used to measure PCC and the quality of health care. We recruited 12 standardized patients from local communities presenting fixed cases (unstable angina and asthma), including 492 interactions between physicians and standardized patients across 63 CHCs in Xi'an, China. PCC was scored on three dismissions: (1) exploring disease and illness experience, (2) understanding the whole person, and (3) finding common ground. We measured the quality of the primary care by (1) accuracy of diagnosis, (2) consultation time, (3) appropriateness of treatment, (4) unnecessary exams; (5) unnecessary drugs, and (6) medical expenditure. Ordinary least-squares regression models with fixed effects were used for the continuous variables and logistic regression models with fixed effects were used for the categorical variables. Results The average score of PCC1, PCC2, and PCC3 was 12.24 ± 4.04 (out of 64), 0.79 ± 0.64 (out of 3), and 10.19 ± 3.60 (out of 17), respectively. The total score of PCC was 23.22 ± 6.24 (out of 84). We found 44.11% of the visits having a correct diagnosis, and 24.19% of the visits having correct treatment. The average number of unnecessary exams and drugs was 0.91 ± 1.05, and 0.45 ± 0.82, respectively. The average total cost was 35.00 ± 41.26 CNY. After controlling for the potential confounding factors and fixed effects, the PCC increased the correct diagnosis by 10 percentage points (P < 0.01), the correct treatment by 7 percentage points (P < 0.01), the consultation time by 0.17 min (P < 0.01), the number of unnecessary drugs by 0.03 items (P < 0.01), and the medical expenditure by 1.46 CNY (P < 0.01). Conclusions This study revealed pretty poor communication between primary care providers and patients. The PCC model has not been achieved, which could be one source of the intensified physician-patient relationship. Our findings showed the PCC model in the primary care settings has positive associations with the quality of the primary care. Interactions with a higher score of PCC were more likely to have a correct diagnosis and correct treatment, more consultation time, more unnecessary drugs, and higher medical expenditure. To improve PCC, the clinical capacity and communication skills of primary care providers need to be strengthened. Also, strategies on reforming the pay structure to better reflect the value of physicians and providing a stronger motivation for performance improvement are urgently needed.